Performance of Groundwater Irrigation System as Perceived by Farmers in West Bengal (Indian Journal of Extension Education, 2022)
In spite of being the most fundamental stakeholder, farmers often receive least attention for assessment of irrigation performance. Present study assessed the performance of groundwater irrigation systems being managed by water user associations (WUAs) in Burdwan (East) district of West Bengal from the perspectives of farmers during the year 2019. A random sample of 120 famers under four groundwater irrigation systems perceived that most of the parameters of irrigation performance in term of irrigation service utility at a higher level with mean perception score >4.0 except for the certainty of water delivery (2.67) leading to overall mean perception score 4.12 in kharif season. Farmers perceived similarly in rabi season with overall mean perception score 4.15; however, the overall perception of farmers regarding irrigation in summer season was relatively low (3.78). Overall irrigation performances under the jurisdiction of WUAs was perceived very good by all the farmers for all three seasons with index values more than 93 per cent. The farmers’ participation in irrigation management has helped in better water management that advocates for promoting participatory irrigation management through WUAs in all the minor irrigation systems to overcome low irrigation efficiency and other management constraints being faced in irrigated areas.